The Peculiarities of Motivation for Applying for Master's Level Studies Referring to Gender, Age, Graduated University and Academic Records - Ina Marija Šeščilienė; Ilona Tilindienė (Lithuanian Sports University, 2018)
The reform of education system and therefore the reform of higher education system became necessary after Lithuania had become an independent country. Since 1991 we have had a three-level system of higher education (studies of Bachelor, Master and Doctoral degrees). Discussions about learning motivation of adults are not so frequent in higher education didactics. We feel duration of theoretical and empirical research in this field, thus our article is devoted to present a little segment of the long-lasting research about evaluation of changes in structure of students' learning motivation for Master's level studies. The aim of this article is to discuss the motives for enrolment to the Lithuanian Academy of Physical Education (LAPE) Master's studies in 2003, referring to such criteria as graduated university, age, gender and academic records of Bachelor's studies. 253 persons who had officially applied for enrolment to the LAPE and agreed to fill in the questionnaire. In the study the following research methods were applied - questionnaire survey, statistical analysis. Some differences of female and male, older and younger persons were determined investigating peculiarities of motivation for applying for Master's studies at the Lithuanian Academy of Physical Education. Keywords: graduate studies, motivation for applying for studies.